Evaluating the Effect of Surgical Skill on Outcomes for Laparoscopic Sleeve Gastrectomy: A Video-based Study. Issue 4 (April 2021) - Varban, Oliver A.; Thumma, Jyothi R.; Finks, Jonathan F.; Carlin, Arthur M.; Ghaferi, Amir A.; Dimick, Justin B.
Abstract : Background: Prior studies have demonstrated a correlation between surgical skill and complication rates after laparoscopic Roux-en-Y gastric bypass. However, the impact of surgical skill on a similar but less technically challenging procedure such as sleeve gastrectomy (SG) is unknown. Methods: Practicing bariatric surgeons (n = 25) participating in a statewide quality improvement collaborative submitted an unedited deidentified video of a representative laparoscopic SG. Videos were obtained between 2015 and 2016 and were rated by bariatric surgeons in a blinded fashion using a validated instrument that assesses surgical skill. Overall scores were based on a 5-point Likert scale with 5 representing a "master surgeon" and 1 representing a "surgeon-in-training." Risk-adjusted 30-day complication rates, 1-year weight loss among cases performed during the study period, and operative technique were compared between surgeons rated in the top and bottom quartiles according to skill. Results: Surgeon ratings for skill varied between 2.73 and 4.60. Ratings for skill did not correlate with overall 30-day risk-adjusted complication rates (Pearson correlation coefficient, 0.213, P = 0.303). However, surgeons with higher skill ratings had lower rates of specific surgical complications, including postoperative obstruction (0.13% vs 0.3%, P = 0.017), hemorrhage (0.85% vs 1.27%, P = 0.005), and reoperation (0.24% vs 0.92%, P < 0.0001). Surgeons ranked in the top quartile for skill had faster operating times for SG (59.0 vs 82.1 min, P < 0.0001) and higher annual case volumes for both SG and any bariatric procedure (224.3 cases/yr vs 73.4 cases/yr, P = 0.009 and 244.9 cases/yr and 93.9 cases/yr, P = 0.009) when compared with surgeons in the bottom quartile. When comparing operative technique, top rated surgeons were noted to have a higher likelihood of using buttressing (83.3% vs 0%, P = 0.0041) and intraoperative endoscopy (83.3% vs 0%, P = 0.0041). Conclusions: Peer ratings for surgical skill varied for laparoscopic sleeve gastrectomy but did not have a significant impact on overall complication rates. Top rated surgeons had lower rates of obstruction, hemorrhage, and reoperation; however, severe morbidity remained extremely low among all surgeons. Abstract : Supplemental Digital Content is available in the text